2015
DOI: 10.5194/tc-9-357-2015
|View full text |Cite
|
Sign up to set email alerts
|

Comparing C- and L-band SAR images for sea ice motion estimation

Abstract: Abstract.Pairs of consecutive C-band synthetic-aperture radar (SAR) images are routinely used for sea ice motion estimation. The L-band radar has a fundamentally different character, as its longer wavelength penetrates deeper into sea ice. L-band SAR provides information on the seasonal sea ice inner structure in addition to the surface roughness that dominates C-band images. This is especially useful in the Baltic Sea, which lacks multiyear ice and icebergs, known to be confusing targets for L-band sea ice cl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…Results by [14] indicate that L-band based drift estimates are superior to C-band image estimates. However, inclusion of large proportions of multi-year ice or open ice with less than 30 % sea ice might affect these results ( Fig.…”
Section: Seasonal Drift Comparisonmentioning
confidence: 96%
See 2 more Smart Citations
“…Results by [14] indicate that L-band based drift estimates are superior to C-band image estimates. However, inclusion of large proportions of multi-year ice or open ice with less than 30 % sea ice might affect these results ( Fig.…”
Section: Seasonal Drift Comparisonmentioning
confidence: 96%
“…5a and b). Moreover, [14] argue that multi-year ice inclusions as well as sea ice concentrations below 60% may affect the L-band estimates unfavourably.…”
Section: A Drift Speed Comparisonmentioning
confidence: 99%
See 1 more Smart Citation
“…SAR is widely used based on its all season capability for sea ice monitoring and C-band SAR has traditionally been used to monitor both sea ice extent, concentration, and drift speed [e.g., Walker et al, 2006;Maillard et al, 2005;Karvonen et al, 2007]. Work by Dierking and Busche [2006], Eriksson et al [2010] and Lehtiranta et al [2015] has identified that other SAR frequencies can contribute important information for sea ice classification. Sea ice studies comparing backscatter signatures using multiple frequencies have been carried out by Drinkwater et al [1991], Beaven et al [1993], Eriksson et al [2010], Dierking [2010aDierking [ , 2010b, Brath et al [2013], , and .…”
Section: Introductionmentioning
confidence: 99%
“…Wang and others, 2017) and sea-ice drift estimation (e.g. Korosov and Rampal, 2017; Lehtiranta and others, 2015). C-band (wavelength 3.75–7.5 cm) is the preferred frequency used for operational monitoring of sea ice with SAR as it offers good discrimination between ice types and ice water contrast during summer (Carsey, 1992; Geldsetzer and others, 2015).…”
Section: Introductionmentioning
confidence: 99%